Higher homocysteine and lower betaine increase the risk of microangiopathy in patients with diabetes mellitus carrying the GG genotype of PEMT G774C - Chen, Li; Chen, Yan-ming; Wang, Li-jun; Wei, Jun; Tan, Yao-zong; Zhou, Jing-ya; Yang, Yang; Chen, Yu-ming; Ling, Wen-hua; Zhu, Hui-lian (Diabetes/metabolism research and reviews, 2013)
Background Diabetes represents one of the greatest medical and socioeconomic threats worldwide. The pathogenesis involved is complicated. The effect of methyl donors and genetic polymorphisms in metabolic enzymes on the risk of microangiopathy in patients with diabetes is not well understood. This study investigates the association of homocysteine, choline and betaine levels and phosphatidylethanolamine N‐methyltransferase (PEMT) G774C (rs12325817) genotypes with the risk of diabetes and its related microangiopathic complications. Methods Between January 2009 and June 2010, 184 diabetic patients and 188 non‐diabetic control subjects were enrolled in the hospital‐based case‐control study. Serum concentrations of betaine and choline were determined by high‐performance liquid chromatography (HPLC)–mass spectrometry. Serum concentrations of homocysteine were assayed using HPLC. PEMT gene mutations were detected by polymerase chain reaction and restriction fragment length polymorphism. Results After adjustment for potential confounders, serum total homocysteine had a significant dose‐dependent positive association, and serum choline had an inverse association with the risks of diabetes and its microangiopathic complications (both p < 0.001). Although serum betaine was not associated with the risk of diabetes, it had a significant inverse association with diabetic microangiopathy. Compared with GG genotype, the CC genotype of PEMT G774C was associated with a decreased risk of diabetes (OR 0.559, 95% CI 0.338, 0.926) and its microangiopathy (OR 0.452, 95% CI 0.218, 0.937). Conclusion The GG genotype of the PEMT G774C polymorphism, higher levels of serum homocysteine and lower levels of serum betaine are associated with an increased risk of microangiopathy in patients with diabetes. Copyright © 2013 John Wiley & Sons, Ltd.